Transcending Neoliberalism; Community-Based Development in Latin America - Judson, Fred (Labour / Le Travail, 2004)
The article reviews the book, "Transcending Neoliberalism; Community-Based Development in Latin America," edited by Henry Veltmeyer and Anthony O'Malley.